Fluency profile: comparison between Brazilian and European Portuguese speakers - Martins-Reis, Vanessa (2014)
The purpose of the study was to compare the speech fluency of Brazilian Portuguese speakers with that of European Portuguese speakers. The study participants were 76 individuals of any ethnicity or skin color aged 18–29 years. Of the participants, 38 lived in Brazil and 38 in Portugal. Speech samples from all participants were obtained and analyzed according to the variables of typology and frequency of speech disruptions and speech rate. Descriptive and inferential statistical analyses were performed to assess the association between the fluency profile and linguistic variant variables. We found that the speech rate of European Portuguese speakers was higher than the speech rate of Brazilian Portuguese speakers in words per minute (p=0.004). The qualitative distribution of the typology of common dysfluencies (p<0.001) also discriminated between the linguistic variants. While a speech fluency profile of European Portuguese speakers is not available, speech therapists in Portugal can use the same speech fluency assessment as has been used in Brazil to establish a diagnosis of stuttering, especially in regard to typical and stuttering dysfluencies, with care taken when evaluating the speech rate.